2022
DOI: 10.4236/ojbm.2022.106159
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Social Media for SME Growth in the Covid-19 Era: A Case of SMEs in the Clothing industry in Lusaka, Zambia

Abstract: Social media has become an emerging integral component to any business in the COVID-19 era. This study on social media adoption by SMEs in the COVID-19 era using the VT4 framework is thus essential. This study sought to investigate how the VT4 influences social media adoption and growth of SMEs. A quantitative research design was used to carry out this study. The target population of the study was SMEs staff in the clothing industry in Lusaka. A structured questionnaire was used as the data collection tool on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…A more or less similar study by Apenteng and Doe (2014) in Ghana established that use of social media enables SMEs to reach greater market including outside markets at low costs. In Zambia, Kakumbi & Phiri (2022) found that adoption of social media by SMEs made it possible for SMEs to be more visible and to communicate more with clients, communicate their products and be able to market their products using prominent people. In turn, SMEs were also able to create ties and to get feedback from clients.…”
Section: Estimation Model Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A more or less similar study by Apenteng and Doe (2014) in Ghana established that use of social media enables SMEs to reach greater market including outside markets at low costs. In Zambia, Kakumbi & Phiri (2022) found that adoption of social media by SMEs made it possible for SMEs to be more visible and to communicate more with clients, communicate their products and be able to market their products using prominent people. In turn, SMEs were also able to create ties and to get feedback from clients.…”
Section: Estimation Model Resultsmentioning
confidence: 99%
“…Use of social media has also an influence on innovation and branding in SMEs. However, as Kakumbi and Phiri (2022) have observed, most SMEs have not been generally enthusiastic in their involvement with electronic commerce. In Tanzania there is paucity of information on the relationship between social media and performance of SMEs.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations